Understanding Colorectal Cancer Screening Barriers in Saudi Arabia: Insights From a Cross-Sectional Study - Alhassan NS; Beyari MB; Aldeligan SH; Alqusiyer AA; Almutib SA; Alarfaj MA; Abdulla MH; Bin Traiki T (Journal of Multidisciplinary Healthcare)
Noura S Alhassan,1 Mohammed Basem Beyari,2 Saleh Husam Aldeligan,2 Abdulaziz Abdulmuhsin Alqusiyer,2 Shatha Abdulaziz Almutib,2 Mohammed Ahmed Alarfaj,2 Maha Hamadien Abdulla,1 Thamer Bin Traiki1 1Department of Surgery, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Mohammed Basem Beyari, Email Mohammedbeyari44@gmail.comIntroduction: Colorectal cancer is a significant health concern in Saudi Arabia, ranking among the most common cancers and often presenting at advanced stages due to low early detection rates. Despite available screening tools, many cases are diagnosed late, leading to poor outcomes. The importance of early detection through screening cannot be overstated as it significantly improves prognosis and reduces mortality.Methods: This study was conducted as a cross-sectional survey in Riyadh from January to July 2024. It aimed to assess awareness and barriers to colorectal cancer screening among the general public. A self-administered questionnaire was distributed, yielding 768 eligible responses after applying exclusion criteria.Results: The results revealed that, while 88% of respondents were aware of colorectal cancer, only 16% had undergone screening tests primarily via colonoscopy. Significant barriers to screening included a lack of physician recommendation, absence of a comprehensive national screening program and fear of complications from colonoscopy. Females were more likely to experience embarrassment and fair of pain as barriers compared to males. Additionally, residents of rural areas faced challenges related to the avalanche of screening facilities.Conclusion: These findings underscore the need for targeted public health interventions, including enhanced awareness campaigns and the development of a national CRC screening program to increase early detection rates and reduce the burden of colorectal cancer in Saudi Arabia.Keywords: colon cancer screening, barriers, awareness